Performance Evaluation of The Extension Worker and The Development Strategy of Organic Agriculture Extension in Batu City - Hendro Prasetyo; Lilis Hariani (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2018)
The area of Batu City generally performs high agricultural productivity. Batu is known as a producer of food and horticultural commodities that meet the needs of other regions. However, an excessive use of chemical pesticides and fertilizers in agricultural land has resulted in reducing land quality and productivity. Regarding such issues, the municipal government of Batu city encourages the implementation of organic farming. The role of extension workers is expected to be able to provide implementation up to the level of farmer cultivation management. The objectives of this study include (1) evaluating the performance of agricultural extension services, (2) identifying the internal and external environment of the organic agriculture extension program, (3) analyzing the strategy for developing an organic agriculture extension program. The study was conducted in the District of Junrejo Bumiaji Batu. Farmers and key persons were interviewed to obtain perceptual variables on the performance of extension workers, and strategies to increase the role of extension workers. The results of this study indicate that the performance of agricultural extension in seven indicators is sufficient. Only one indicator that has unsatisfactory performance is the media used in education counseling. Strategies for increasing the role of extension workers include: (1) improving information about organic agriculture by improving extension methods, (2) increasing the ability of farmer groups by working with stakeholders, (3) improving more effective and efficient extension methods, (4) improving the number of extension agents to optimize services for farmers, and (5) improving the quality of extension workers.JEL Classification: Q16, Q58, Q56